Engineering Properties of Durian Seed Strach (Durio zibethinus Murr.) Resulted from Convection Oven Drying - Dian Purbasari; Dini Suharyati Iskandar (The University of Lampung, 2025)
Durian seed is part of the durian fruit that has many benefits but are often considered useless. Durian seeds have the potential to be developed for its use because it contains high starch. This study analyzes the physical characteristics of durian seed starch from convection oven drying. This study used a completely randomized design with two factorials: deposition time (24 and 48 h) and drying temperature (60, 70, and 80℃). Durian seed starch was processed by drying and crushing, then sieved with 100 mesh size. The data analysis used was a two-way ANOVA test followed by Duncan's. The results of ANOVA analysis of different drying temperatures affect the value of water content, yellowness (b), grain average (D), water absorption (DSA), and yield. At the same time, the length of deposition in the process of making starch affects the value of yield variables. The results of durian seed starch characterization resulted in the highest moisture content value of 6.26%; brightness value of 92.92; reddish value of 2.06; yellowish value of 2.24; water absorption value of 1.28 ml/g; and yield value of b16.03%. Keywords: Convection oven, Drying, Durian seed, Starch.